Volatility behavior patterns and information transmission mechanism : evidence from Malaysian futures markets - Ahmad, Noryati (2005)
This study employs bivariate ARMA(p,q)-EGARCH(p,q) model specifications model to investigate whether information between Malaysian futures and cash markets is transmitted through first moments or second moments or both. Using daily data, the study covers the period from January 2, 1990 until December 31, 2003. The study also investigates the effects of the Malaysian futures - cash market relationship in the light of international market interdependencies. More specifically, it looks at whether information from foreign futures markets of S&P SOO, HSIF and NSIF influence the futures-cash relationship and whether the effects come through price level or volatility or both. In addition, the study also looks at the volatility patterns of Malaysian futures markets in order to facilitate a better understanding of the volatility transmission process. Lastly, to determine whether this transmission of information process (be it within and across markets) is affected by structural changes, the sample period was sub -divided into pre-crisis, during-crisis and post-crisis periods. Results indicate that the volatility behavior patterns of FKLI and FCPO futures markets are highly persistent but mean-reverting. Volatility of these futures markets also reacted asymmetrically to its past innovations, where positive news caused higher volatility than negative news. Transmission of information between Malaysian futures and cash markets occurs at both returns and volatility level, where futures markets tend to dominate the cash market at both levels. Volatility transmission is not asymmetric when the interactions between the futures and cash markets are included. The error correction terms have significant predictive power on both the conditional mean and volatility of these futures markets. Findings show that domestic futures-cash relationship is being influenced by the information transmitted from foreign futures markets. As for the Malaysian stock index futures, S&P 500 futures is the information producer at return level, while HSIF futures is at volatility level. NSIF futures have no influence on the volatility of FKLI and its related cash markets